2013 Lippincott's nursing drug guide - Karch, Amy Morrison , 1949- (Wolters Kluwer/Lippincott Williams & Wilkins, 2013)
A comprehensive guide for nursing students and practicing nurses, the 2013 Lippincott's Nursing Drug Guide provides quick A-to-Z access to current, vital drug information